The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5424/sjar/2014123-4948
|View full text |Cite
|
Sign up to set email alerts
|

Use of endometrial cytology and metabolic profiles for selection of embryo donor cows

Abstract: The aim of this study was to evaluate the use of endometrial cytology and metabolic profiles for selection of donor cows in embryo transfer programmes. For this purpose, 69 clinically healthy Holstein cows were enrolled in the study. At the start of the superovulation procedure (Day 0), blood and endometrial samples were obtained to determine metabolic and uterine status, respectively. The cows were then subjected to porcine follicle stimulating hormone (pFSH) superovulation treatment, and embryos were recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…Independently of the cause of inflammation, the inflammatory status of the endometrium may have a major impact on reproduction. A direct negative effect of SE on embryo quality and survival has already been described [39,40], which would affect conception rates. In addition, results from various studies suggest that SE may be associated to altered patterns of prostaglandin E 2 and F 2α synthesis [41,42] which could compromise luteal function and pregnancy.…”
Section: Etiopathogenesismentioning
confidence: 95%
“…Independently of the cause of inflammation, the inflammatory status of the endometrium may have a major impact on reproduction. A direct negative effect of SE on embryo quality and survival has already been described [39,40], which would affect conception rates. In addition, results from various studies suggest that SE may be associated to altered patterns of prostaglandin E 2 and F 2α synthesis [41,42] which could compromise luteal function and pregnancy.…”
Section: Etiopathogenesismentioning
confidence: 95%
“…Several studies showed negative effects of SE on fertility after AI (4,5,8,34,54), and the same have been described on embryo quality in donor cows. Carvalho et al (12) and Fernandez-Sanchez et al (18) reported a significant reduction in the percentage of viable embryos in cows with high endometrial PMN at the onset of superovulation. Drillich et al (17) investigated PMN dynamics in the endometrium of donor cows from AI to the time of flush (day 7) and found a significant relationship between them and the flushing outcome.…”
Section: Et In Repeat Breeder Cowsmentioning
confidence: 97%
“…Globulin (haptoglobulin) dapat menjadi salah satu indikator status kesehatan, reproduksi, dan produktivitas sapi perah (Banos et al, 2013). Profil protein total dan albumin pada sapi dapat digunakan sebagai dasar seleksi sapi donor sebelum produksi embrio (Fernandez-Sanchez et al, 2014). Penelitian mengenai profil proteinogram sebelum produksi embrio pada sapi donor PO belum pernah dilakukan.…”
Section: Pendahuluanunclassified